Integrating the development agenda with noncommunicable disease prevention in developing countries: a quasi-experimental study on inter-sectoral action and its impact on self-reported salt consumption—the INPARD study - Liyanage, I.K.; Wickramasinghe, K.; Katulanda, P.; Jayawardena, R.; Karunathilake, I.M.; Friel, S.; Manoharan, S.; Pathirana, A.; Alagiyawanna, A.; Ranaweera, N.; Townsend, N. (Cardiovascular Diagnosis and Therapy, 2019)
Background: The determination of behaviours that lead to noncommunicable diseases (NCDs), such as high dietary salt intake, are multifactorial. The prevention of NCDs, including the promotion of healthy dietary choice, including low salt intake, therefore requires multisectoral working. Although the need of a multisectoral approach to risk factor modification has been globally accepted, there is minimal evidence for its application in the real world. Methods: This quasi-experimental trial was designed to study the impact of a community led multisectoral approach to integrate nutrition prevention into the development agenda, in two districts in Sri Lanka, a lower-middle income country undergoing a phase of rapid socioeconomic development. Results: Results from logistic regression found that those living in the district (Ampara) that identified salt intake as a health issue had significantly higher odds (OR =1.4; 95% CI =1.1, 1.9) of high salt consumption (>5 grams/day) at baseline compared to control areas (Kurunegala), in multivariable models. Postintervention, individuals in this district had lower odds (OR =0.6; 95% CI =0.4, 0.9) of consuming high levels of salt in all models, including multivariable models whilst controlling for baseline high salt consumption. Conclusions: The findings from this study demonstrate the positive impact in improved diet, in reduced salt consumption, through a community-led multisectoral intervention, in areas in which the community identified high salt consumption as a health issue. These findings demonstrate that multisectoral approaches can be effective in the real world setting and highlight the need to engage with many stakeholders, including targeted communities throughout their development and implementation.
Keywords: Multisectoral; diet; noncommunicable diseases (NCDs); salt; low and middle-income countries